2017
DOI: 10.1124/dmd.117.075994
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion–Transporting Polypeptide (OATP)–Mediated Drug-Drug Interaction Study between Rosuvastatin and Cyclosporine A in Chimeric Mice with Humanized Liver

Abstract: The influence of transporters on the pharmacokinetics of drugs is being increasingly recognized, and DDIs via transporters may be a risk factor for adverse events. Cyclosporine A, a strong OATP inhibitor, has been reported to increase the systemic exposure of rosuvastatin, an OATP substrate, by 7.1-fold in clinical studies. PXB mice are chimeric mice with humanized livers that are highly repopulated with human hepatocytes and have been widely used for drug discovery in drug metabolism and pharmacokinetics stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Early studies have found that cyclosporine A can inhibit OATP1B1-mediated transport of cerivastatin, which increases the concentration of cerivastatin in vivo and changes the distribution of cerivastatin in vivo 22 . OATP mediates rosuvastatin transportation, cyclosporine A can competitively inhibit the uptake of rosuvastatin by the hepatocyte membrane OATP and thus increases drug plasma concentration 23 . Studies have also found that Salvianic acid A can inhibit OATP1B1 by competition, thus affecting the pharmacokinetic characteristics of rosuvastatin in rats 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have found that cyclosporine A can inhibit OATP1B1-mediated transport of cerivastatin, which increases the concentration of cerivastatin in vivo and changes the distribution of cerivastatin in vivo 22 . OATP mediates rosuvastatin transportation, cyclosporine A can competitively inhibit the uptake of rosuvastatin by the hepatocyte membrane OATP and thus increases drug plasma concentration 23 . Studies have also found that Salvianic acid A can inhibit OATP1B1 by competition, thus affecting the pharmacokinetic characteristics of rosuvastatin in rats 24 .…”
Section: Discussionmentioning
confidence: 99%
“…258,259 Lastly, the drug-drug interactions-which are caused by competition over CYP enzymes, non-CYP enzymes, and transporters-occurring in the liver of HLCM well resemble that of the human liver. 97,[260][261][262] Collectively, HLCM most accurately reiterates the DMPK of the human liver and justifies its superiority over other in vitro and in vivo study tools. 96,263,264 Drug-Induced Liver Injury…”
Section: Drug Metabolism and Pharmacokineticsmentioning
confidence: 97%
“…Quinidine has been shown to inhibit the CYP2D6‐mediated metabolism of debrisoquin, and ritonavir has been reported to reduce the CYP3A4‐mediated metabolism of clemizole in humanized mice (Katoh et al, ; Nishimura et al, ). In a transporter DDI study in humanized mice, cyclosporine A effectively inhibited the OATP‐mediated uptake of rosuvastatin in a dose dependent manner (Uchida et al, ). Similar to humans, the humanized mice gave a higher oral plasma AUC than for intravenous administration, suggesting the gut contribution to DDI.…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%
“…Similar to humans, the humanized mice gave a higher oral plasma AUC than for intravenous administration, suggesting the gut contribution to DDI. However, the presence of mouse gut transporters complicated the data interpretation of liver OATP DDI (Uchida et al, ).…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%